-2
$\begingroup$

Prove that $$\frac{1}{\sqrt{1-\sin^2{x}}}=\sum_{n=0}^{\infty} \frac{(2n)!(\sqrt{\sin{x}})^{4n}}{4^n (n!)^2}$$

$\endgroup$
  • 1
    $\begingroup$ Do you mean: $$\frac{1}{\sqrt{1-\sin^2{x}}}=\sum_{n=0}^{\infty} \frac{(2n)!(\sqrt{\sin{x}})^{4n}}{4^n (n!)^2}$$ $\endgroup$ – projectilemotion Apr 1 '17 at 16:33
  • $\begingroup$ Yes👍👍👍☝☝☝☝☝☝☝☝☝☝☝☝☝☝☝☝👍👍 $\endgroup$ – creedoos Apr 1 '17 at 16:48
  • $\begingroup$ Ok, the ambiguity of the problem is now settled. What are your thoughts and what have you tried to solve the problem? That way, we don't repeat information you already know. $\endgroup$ – projectilemotion Apr 1 '17 at 16:53
0
$\begingroup$

Hint. One may use the generalized binomial theorem (see here) to get, $$\begin{eqnarray*} \frac{1}{\sqrt{1-u}}=(1-u)^{-1/2}=\sum_{n=0}^\infty \frac{{2n\choose n}}{2^{2n}}u^{n} &, \qquad |u|<1, \end{eqnarray*}$$ then one may put $u:=\sin^2 x$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.